PERAN METODE DISKUSI FIQIH DALAM MENINGKATKAN BERFIKIR KRITIS SANTRI DI PONDOK PESANTREN ANNUR AL-HUDA NGAWONGGO TAJINAN MALANG - Ahmat Fahruddin; Yazidul Busthomi; Zainuddin Fanani (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the role of the fiqh discussion method in improving the critical thinking skills of students at the Annur Al-Huda Ngawonggo Islamic Boarding School in Tajinan Malang. The background of the research is the low participation and interest of students in learning fiqh which has been dominated by conventional lecture methods. The research used a descriptive qualitative approach with data collection techniques through observation, interviews, documentation, and questionnaires. The research subjects involved 50 fiqh students and ustadz who applied the structured discussion method. The results showed that the four-stage-based discussion method (introduction of issues, search for legal sources, structured discussion, and preparation of recommendations) was able to improve the critical thinking skills of students. As many as 72% of the students were able to identify global-local issues (such as inflation and the value of zakat), and 68% used the maqashid sharia framework to analyze crypto assets. The division of roles in the discussion (guide, law interpreter, conclusion formulator) improved collaboration and learning effectiveness. However, challenges such as heterogeneity of basic competencies and blind taqlid were still encountered, which were addressed through contextual strategies and collaborative mentoring. The research conclusion proves that the structured fiqh discussion method not only improves santri's analytical and argumentation skills, but also bridges classical studies with modern realities. The practical implications include the development of contextual learning modules, integration of simple analytical tools, and collaboration between pesantren. These findings contribute to the innovation of critical fiqh education in the pesantren environment, while strengthening the relevance of Islamic science in responding to the challenges of the disruption era.